2019
DOI: 10.1111/soru.12230
|View full text |Cite
|
Sign up to set email alerts
|

Being a poor farmer in a wealthy country: A Swiss case study

Abstract: Many Swiss farming families face socioeconomic disadvantage despite Switzerland being a wealthy country with instruments of agricultural policy financially supporting almost all farmers. However, official poverty statistics exclude Swiss farmers and scientific knowledge is rare about how such situations are experienced. This article scrutinises the situation of Swiss farming families living in poverty or material deprivation by intertwining qualitative and quantitative methods to enrich both types of data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
0
4
0
3
Order By: Relevance
“…This occurs despite the fact that Switzerland is a wealthy country with efficient instruments of agrarian policy. In eleven out of 32 interviews, respondents indicated that they had to be very careful in managing their food expenses and that self-sufficiency is a way to contain costs [43].…”
Section: Figurementioning
confidence: 99%
“…This occurs despite the fact that Switzerland is a wealthy country with efficient instruments of agrarian policy. In eleven out of 32 interviews, respondents indicated that they had to be very careful in managing their food expenses and that self-sufficiency is a way to contain costs [43].…”
Section: Figurementioning
confidence: 99%
“…Australia, Chile, and New Zealand) but with a limited social safety net compared to most other Western industrialized nations. Yet, research from Europe, Canada, and Australia indicates that even with stronger social policies, farm households experience challenges meeting their social and economic needs (Chappuis et al 2015;Contzen and Crettaz 2019;Contzen et al 2016;Courtenay Botterill 2007;Droz et al 2014;Roche 2016). Collectively, these findings reinforce contemporary calls (Becot and Inwood 2020;Darnhofer 2021) to expand the types of issues and variables farm family scholars study.…”
Section: Discussionmentioning
confidence: 99%
“…Perubahan tersebut dicirikan oleh adanya perubahan pada struktur sosial yang dapat dilihat dari perubahan pada struktur agraria yang semula bersifat komunal menjadi individual dan pola pemanfaatan sumberdaya alam yang berlandaskan kearifan local menjadi berlandaskan inovasi baru. Struktur sosial juga melihat perubahan pada strategi nafkah yang pada awalnya berbasis pada pertanian untuk memenuhi kebutuhan subsistensi akan pangan menjadi berbasis pada pertanian dan non pertanian yang bersifat komersial (Contzen & Crettaz, 2019). Perubahan pada supra struktur sosial juga diperlihatkan pada etika moral ekonomi masyarakat tani yang sebelumnya lebih dominan pada moral ekonomi petani pada masyarakat yang tradisional menjadi politik ekonomi petani pada masyarakat tani yang termodernisasi (Mardiyaningsih et al, 2010).…”
Section: Hasil Dan Pembahasanunclassified